STUDY ON THE CONCENTRATION EFFECT OF Nb2O5-ZAA CATALYST TOWARDS TOTAL CONVERSION OF BIODIESEL IN TRANSESTERIFICATION OF WASTED COOKING OIL - Astuti Tri Padmaningsih; Wega Trisunaryanti; Iqmal Tahir (Universitas Gadjah Mada, 2006)
Study on the concentration effect of Nb2O5-ZAAcatalyst towards total conversion of biodiesel has been conducted. The natural zeolite (ZA) was activated by dipping in NH4Cl solution and was calcined using N2 atmosphere at 500 °C for 5h to produce the ZAA sample. The Nb2O5-ZAA catalyst was made by mixing the activated natural zeolite (ZAA), Nb2O5 3 % (w/w) and oxalic acid 10 % (w/w) solution, until the paste was formed, followed by drying and calcining the catalyst for 3 h at 500 °C under N2 atmosphere. Catalyst characterizations were conducted by measuring acidity with NH3 gas using gravimetric method and porosimetric analysis using N2 gas adsorption based on the BET equation by surface area analyzer instrument. The Nb2O5-ZAA catalyst was then used as an acid catalyst in free fatty acid esterification reaction of wasted cooking oil in methanol medium with variation of catalyst concentration: 1.25%; 2.5%; 3.75% and 5% towards the weight of oil+methanol. The reaction was continued by transesterification of triglyceride in the used cooking oil using NaOH catalyst in methanol medium. For comparison, the esterification reaction using H2SO4 catalyst 1.25% towards the weight of oil+methanol has been conducted as well. Methyl ester (biodiesel) product was analyzed using Gas Chromatography (GC) and Gas Chromatography-Mass Spectrometry (GC-MS). The characters of biodiesel were analyzed using American Society for Testing and Materials (ASTM) method. The results showed that modification of ZAA by impregning Nb2O5 3% (w/w) increased the total catalyst acidity from 5.00 mmol/g to 5.65 mmol/g. The Nb2O5-ZAA catalyst has specific surface area of 60.61 m2/g, total pore volume of 37.62x10-3 cc/g and average pore radius of 12.41 Å. The Nb2O5-ZAAcatalyst with concentration of 1.25%-5% produced higher total conversion of biodiesel than that of H2SO4 catalyst 1.25%. The Nb2O5-ZAA catalyst with concentration of 3.75% produced the highest total conversion of biodiesel, i.e. 76.76 %. Based on the ASTM data analysis, the product has a qualification as diesel fuel.